Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's tackle the problem step-by-step.
Given the quadratic equation:
[tex]\[ x^2 - kx - 28 = 0 \][/tex]
We know one of the roots is [tex]\( -7 \)[/tex]. Let's denote the roots of the quadratic equation by [tex]\( r_1 \)[/tex] and [tex]\( r_2 \)[/tex].
Step (i): Find the value of [tex]\( k \)[/tex]
First, we know from Vieta's formulas that for a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
1. The sum of the roots [tex]\( r_1 + r_2 = -\frac{b}{a} \)[/tex]
2. The product of the roots [tex]\( r_1 \cdot r_2 = \frac{c}{a} \)[/tex]
For our given equation [tex]\( x^2 - kx - 28 = 0 \)[/tex]:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = -k \)[/tex]
- [tex]\( c = -28 \)[/tex]
We are given [tex]\( r_1 = -7 \)[/tex]. Let's denote [tex]\( r_2 \)[/tex] as the other root.
By Vieta's formulas:
[tex]\[ r_1 \cdot r_2 = -28 \][/tex]
Substitute [tex]\( r_1 = -7 \)[/tex]:
[tex]\[ -7 \cdot r_2 = -28 \][/tex]
Solve for [tex]\( r_2 \)[/tex]:
[tex]\[ r_2 = \frac{-28}{-7} = 4 \][/tex]
Now, using the sum of the roots:
[tex]\[ r_1 + r_2 = -\frac{b}{a} \][/tex]
Substitute [tex]\( r_1 = -7 \)[/tex] and [tex]\( r_2 = 4 \)[/tex]:
[tex]\[ -7 + 4 = -\frac{-k}{1} \][/tex]
[tex]\[ -3 = -k \][/tex]
[tex]\[ k = 3 \][/tex]
So, the value of [tex]\( k \)[/tex] is [tex]\( 3 \)[/tex].
Step (ii): Find the other root
We already found in the previous calculation that the other root [tex]\( r_2 \)[/tex] is:
[tex]\[ r_2 = 4 \][/tex]
Summary:
- The value of [tex]\( k \)[/tex] is [tex]\( 3 \)[/tex].
- The other root of the equation is [tex]\( 4 \)[/tex].
Given the quadratic equation:
[tex]\[ x^2 - kx - 28 = 0 \][/tex]
We know one of the roots is [tex]\( -7 \)[/tex]. Let's denote the roots of the quadratic equation by [tex]\( r_1 \)[/tex] and [tex]\( r_2 \)[/tex].
Step (i): Find the value of [tex]\( k \)[/tex]
First, we know from Vieta's formulas that for a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
1. The sum of the roots [tex]\( r_1 + r_2 = -\frac{b}{a} \)[/tex]
2. The product of the roots [tex]\( r_1 \cdot r_2 = \frac{c}{a} \)[/tex]
For our given equation [tex]\( x^2 - kx - 28 = 0 \)[/tex]:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = -k \)[/tex]
- [tex]\( c = -28 \)[/tex]
We are given [tex]\( r_1 = -7 \)[/tex]. Let's denote [tex]\( r_2 \)[/tex] as the other root.
By Vieta's formulas:
[tex]\[ r_1 \cdot r_2 = -28 \][/tex]
Substitute [tex]\( r_1 = -7 \)[/tex]:
[tex]\[ -7 \cdot r_2 = -28 \][/tex]
Solve for [tex]\( r_2 \)[/tex]:
[tex]\[ r_2 = \frac{-28}{-7} = 4 \][/tex]
Now, using the sum of the roots:
[tex]\[ r_1 + r_2 = -\frac{b}{a} \][/tex]
Substitute [tex]\( r_1 = -7 \)[/tex] and [tex]\( r_2 = 4 \)[/tex]:
[tex]\[ -7 + 4 = -\frac{-k}{1} \][/tex]
[tex]\[ -3 = -k \][/tex]
[tex]\[ k = 3 \][/tex]
So, the value of [tex]\( k \)[/tex] is [tex]\( 3 \)[/tex].
Step (ii): Find the other root
We already found in the previous calculation that the other root [tex]\( r_2 \)[/tex] is:
[tex]\[ r_2 = 4 \][/tex]
Summary:
- The value of [tex]\( k \)[/tex] is [tex]\( 3 \)[/tex].
- The other root of the equation is [tex]\( 4 \)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.